Effects of climate change on the breeding ecology and trophic interactions of Arctic-breeding shorebirds - Kwon, Eunbi (Kansas State University, 2016)
Impacts of climate change on biological systems include shifts in seasonal phenology. How do migratory animals adjust reproductive decisions as they shift timing of breeding? I investigated patterns of climate change at a network of Arctic sites in Alaska and Canada, and examined the impacts of climate change on the breeding phenology, reproductive performance, and trophic interactions of Arctic-breeding shorebirds. First, I compared the breeding performance of three species, Western Sandpiper, Semipalmated Sandpiper, and Red-necked Phalaropes, at Nome, Alaska, across a 14-year interval. I found that shorebirds responded to a decreasing temperature during laying by delaying timing of breeding. Delayed breeding shortened the incubation duration for two biparental species but extended incubation for a uniparental species. Despite a short Arctic summer, the breeding windows of three sympatric species were temporally distinct. The three species often nested within several meters from each other, but bred under different temperature regimes and adjusted their reproductive output to different sets of environmental factors. Shifts in breeding phenology can disrupt trophic interactions, especially the phenological match between peak prey availability and hatching of shorebirds. Comparing the extent of phenological mismatch between six shorebirds and their invertebrate prey at ten Arctic sites, peak demand of shorebird broods occurred on average 3.8 days (± 13.8) later than local food peaks, and population demand curves overlapped with food curves by 47% (± 14%). Latitudinal and longitudinal gradients in the extent of trophic mismatch were mediated through geographic variation in the seasonal phenology of invertebrates and shorebirds. For individual nests, both more northerly and easterly sites showed greater phenological mismatch with annual food peaks. Delayed emergence of food peaks at more northerly and easterly sites alleviated the extent of phenological mismatch. My multi-site study provides the first evidence that large-scale geographic processes can determine the extent of phenological mismatch in a bitrophic system. Trends of climate change are sensitive to breeding stages and also vary along a longitudinal gradient. Variability in climatic trends in the Arctic, combined with species-dependent responses to local climate change, indicate that it will be challenging to predict the impacts of future climate change.
Keywords: Breeding phenology; Climate variability; Match-Mismatch hypothesis; Nest survival; Reproductive trait; Space-for-time substitution; Ecology (0329); Zoology (0472)